Images between life and death: reflections from "Resurrection" (1987), by Arthur Omar - Franco, Frederico (Revista do Colóquio, 2024)
This work proposes to analyze how the short film “Ressurreição” (1987), by Arthur Omar, relates to death, through the photographic device. In modernity, the advent of photography suggests new connections between the production of images and death. Is it within this theoretical spectrum, which goes from Walter Benjamin to Roland Barthes, meeting Georges Didi-Huberman, Susan Sontag and Douglas Crimp along the way, that this work will focus on understanding how Arthur Omar and his mortuary photographs deal with death itself? What is the role of the photographic device itself in the relationship proposed here?